Factors influencing the development of nursing professionalism: a descriptive qualitative study - Xingyue He; Ya Mao; Huili Cao; Linbo Li; Yanming Wu; Hui Yang (BMC, 2024)
Abstract Background The shortage of nurses threatens the entire healthcare system, and nursing professionalism can improve nurse retention and enhance the quality of care. However, nursing professionalism is dynamic, and the factors influencing its development are not fully understood. Methods A qualitative descriptive study was conducted. Using maximum variation and purposive sampling, 14 southern and northern China participants were recruited. Semi-structured interviews were conducted from May 2022 to August 2023 in face-to-face conversations in offices in the workplace or via voice calls. The interviews were transcribed verbatim and analyzed via thematic analysis. Results Three main themes emerged: (1) nourishment factors: promoting early sprouting; (2) growth factors: the power of self-activation and overcoming challenges; and (3) rootedness factors: stability and upward momentum. Participants described the early acquisition of nursing professionalism as derived from personality traits, family upbringing, and school professional education, promoting the growth of nursing professionalism through self-activation and overcoming challenges, and maintaining the stable and upward development of nursing professionalism through an upward atmosphere and external motivation. Conclusion We revealed the dynamic factors that influence the development of nursing professionalism, including "nourishment factors", "growth factors", and "rootedness factors". Our findings provide a foundation for future development of nursing professionalism cultivation strategies. Nursing administrators can guide the development of nurses' professionalism from many angles according to the stage they are in, and the development of professionalism deserves more attention. In the future, we can no longer consider the development of nursing professionalism solely as the responsibility of individual nurses; the power of families, organizations, and society is indispensable to jointly promoting nursing professionalism among nurses.